WORKING WITH THE DICTIONARY IN STUDYING TEXTS IN CLASSICAL LITERATURE - B. Abdurahmonova; O. Abdurahmonova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article provides recommendations on the study of the qadi genre in academic lyceums, which is used in classical literature. It has been explained that it is in the study of the Quida genre that research on the basis of dictionaries brings effective results.